Exploring the interplay between mitochondria and endoplasmic reticulum in pulmonary arterial hypertension - Liao, Zhipeng; He, Yuanzhou (Frontiers in Cardiovascular Medicine, 2025)
Pulmonary arterial hypertension (PAH) is a subtype of pulmonary hypertension (PH), characterized by pulmonary arterial remodeling. This disease frequently progresses to right heart failure and can result in patient mortality. Research at the cellular and molecular level is gradually revealing the mechanism underlying the development of pulmonary arterial hypertension, providing new avenues for treatment by identifying potential therapeutic targets. Contact between the endoplasmic reticulum and mitochondria has been recognized for several decades. And an increasing number of laboratory and clinical studies are beginning to elucidate the relationship between PAH and the interplay involving mitochondria and the endoplasmic reticulum. In this review, we first introduce the basic normal biological functions and processes of MAM-based mitochondrial-endoplasmic reticulum interactions. We then discuss how the dysfunction contributes to pulmonary arterial hypertension (PAH), focusing on three key aspects, mitochondrial dynamics, calcium homeostasis, and endoplasmic reticulum stress. Clarifying these issues may provide important insights for therapeutic interventions in PAH.